In situ time‐of‐flight neutron imaging of NiO–YSZ anode support reduction under influence of stress. Issue 5 (16th September 2016) - Makowska, Małgorzata G.; Strobl, Markus; Lauridsen, Erik M.; Kabra, Saurabh; Kockelmann, Winfried; Tremsin, Anton; Frandsen, Henrik L.; Theil Kuhn, Luise
Abstract : Results of the first in situ energy‐resolved neutron imaging of NiO–YSZ (YSZ is yttria‐stabilized zirconia) reduction under applied stress are presented. Neutron experiments were performed at the pulsed neutron source ISIS (UK) using a time‐of‐flight approach. Abstract : This article reports on in situ macroscopic scale imaging of NiO–YSZ (YSZ is yttria‐stabilized zirconia) reduction under applied stress – a phase transition taking place in solid oxide electrochemical cells in a reducing atmosphere of a hydrogen/nitrogen mixture and at operation temperatures of up to 1073 K. This process is critical for the performance and lifetime of the cells. Energy‐resolved neutron imaging was applied to observe the phase transition directly with time and spatial resolution. Two different approaches are presented for using this imaging technique for the investigation of chemical and physical processes requiring controlled atmosphere and elevated temperature. The first type of measurement is based on alternating stages of short‐term partial chemical reaction and longer neutron image acquisition, and the second type is a real in situ neutron imaging experiment. Results of applying energy‐resolved neutron imaging with both approaches to the NiO–YSZ reduction investigation indicate enhancement of the reduction rate due to applied stress, which is consistent with the results of the authors' previous research.